Glove manufacturing method

By using a latex composition containing carboxyl-conjugated diene rubber and metal compound and γ-ray irradiation, the problem of insufficient tensile strength and stress retention during use of gloves is solved, and high tensile strength and elongation are achieved Rate and soft feel.

CN119463228APending Publication Date: 2025-02-18ZEON CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311355174.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2016-11-30
Filing Date
2017-02-24
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing gloves are difficult to maintain sufficient tensile strength and stress retention during use, resulting in poor feel and prone to fatigue.

Method used

By impregnating and molding a latex composition containing a carboxyl-conjugated diene-based rubber without monomer units from isoprene and a metal compound containing a 2-valent or more metal, the formed impregnated molding layer is irradiated with gamma rays. , gloves with high tensile strength, elongation and stress retention are manufactured.

Benefits of technology

The high tensile strength, elongation and soft feel of the gloves are achieved, while improving stress retention and extending the service life of the gloves.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004508339790000241
    Figure BDA0004508339790000241
Patent Text Reader

Abstract

Provided is a method for manufacturing gloves having high tensile strength, high elongation, soft texture, and high stress retention. A method for manufacturing gloves, which comprises a step for forming a dip-molded layer by dip-molding a latex composition that contains a latex of a carboxyl group-containing conjugated diene rubber (A) and a metal compound (B) that contains a divalent or higher metal, and a step for irradiating the dip-molded layer with radiation. In the radiation irradiation step, the irradiation radiation is gamma rays and the amount of absorbed radiation is 1-100 kGy, and the carbon-carbon double bond portion of the conjugated diene monomer unit of the carboxyl group-containing conjugated diene rubber A is crosslinked by the radiation irradiation step, and the conjugated diene monomer unit of the carboxyl group-containing conjugated diene rubber A is crosslinked by the carbon-carbon double bond portion of the conjugated diene monomer unit of the carboxyl group-containing conjugated diene rubber A. The content ratio of the metal compound (B) containing a divalent or higher metal in the latex composition is 0.1-2.0 parts by weight with respect to 100 parts by weight of the carboxyl group-containing conjugated diene rubber (A) contained in the latex.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention patent application with Chinese application number 201780011210.2. The invention name of the original application is “Method for manufacturing gloves” and the application date is February 24, 2017. Technical Field

[0002] The present invention relates to a method for manufacturing gloves, and more particularly to a method for manufacturing gloves having high tensile strength, large elongation, soft hand feeling and high stress retention rate. Background Art

[0003] It has long been known that latex compositions containing natural latex, represented by natural rubber latex, are dip-molded to obtain dip-molded articles such as pacifiers, balloons, gloves, baloons, and covers that are used in contact with the human body. However, since natural rubber latex contains proteins that cause allergic symptoms in the human body, problems often arise when the latex is used as a dip-molded article that is in direct contact with the mucous membrane or internal organs of a living body, especially gloves. Therefore, the use of synthetic nitrile rubber latex is currently being studied.

[0004] For example, Patent Document 1 discloses a latex obtained by copolymerizing 100 parts by weight of a monomer mixture containing 65 to 84.5 parts by weight of a conjugated diene monomer, 15 to 25 parts by weight of an ethylenically unsaturated nitrile monomer, 0.5 to 10 parts by weight of an ethylenically unsaturated acid monomer, and 0 to 19.5 parts by weight of other ethylenically unsaturated monomers copolymerizable with these, and a dip-molded article obtained by dip-molding a latex composition formed by blending sulfur in the latex. The dip-molded article described in Patent Document 1 has an excellent hand feel and sufficient tensile strength, but does not necessarily have a sufficient stress retention rate. In particular, in terms of the fact that the dip-molded article is less likely to cause fatigue (loosening, relaxation) during use of the gloves, it is desirable that the stress retention rate is excellent in addition to the excellent hand feel and sufficient tensile strength.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2003-165814. Summary of the invention

[0008] Problem that the invention aims to solve

[0009] The object of the present invention is to provide a method for manufacturing gloves having high tensile strength, large elongation, soft hand feel and high stress retention rate.

[0010] Solutions for solving problems

[0011] The present inventors have conducted intensive studies to solve the above problems and, as a result, have found that a glove having high tensile strength, high elongation, soft feel and high stress retention can be produced by irradiating a dip-molded layer obtained by dip-molding a latex composition containing a carboxyl group-containing conjugated diene rubber having no monomer unit derived from isoprene and a metal compound containing a divalent or higher-valent metal with radiation such as gamma rays, thereby completing the present invention.

[0012] That is, according to the present invention, there is provided a method for producing a glove, comprising the steps of forming a dip-molded layer by dip-molding a latex composition containing a carboxyl group-containing conjugated diene rubber (A) having no monomer unit derived from isoprene and a metal compound (B) containing a divalent or higher metal, and irradiating the dip-molded layer with radiation.

[0013] In the production method of the present invention, the carboxyl group-containing conjugated diene rubber (A) is preferably at least one selected from the group consisting of carboxyl group-containing nitrile rubber (a1), carboxyl group-containing styrene-butadiene rubber (a2) and carboxyl group-containing butadiene rubber (a3).

[0014] In the production method of the present invention, it is preferred that the metal compound (B) containing a divalent or higher-valent metal contains a metal compound containing a trivalent or higher-valent metal.

[0015] In the production method of the present invention, it is preferred to use a metal compound containing a trivalent or higher valent metal and a metal compound containing a divalent metal in combination as the metal compound containing a divalent or higher valent metal (B).

[0016] In the production method of the present invention, it is preferred that the metal compound containing a trivalent or higher-valent metal is an aluminum compound.

[0017] In the production method of the present invention, the latex composition preferably further contains at least one alcoholic hydroxyl compound (D) selected from sugars (d1), sugar alcohols (d2), hydroxy acids (d3) and hydroxy acid salts (d4).

[0018] In the production method of the present invention, the content of the metal compound (B) containing a divalent or higher metal in the latex composition is preferably 0.1 to 5 parts by weight per 100 parts by weight of the carboxyl group-containing conjugated diene rubber (A) contained in the latex.

[0019] In the production method of the present invention, the latex composition preferably contains sulfur and / or a sulfur-containing compound (C) as a crosslinking agent in a ratio of more than 0 part by weight and not more than 4 parts by weight per 100 parts by weight of the carboxyl group-containing conjugated diene rubber (A) contained in the latex.

[0020] In the production method of the present invention, it is preferred that the irradiation radiation in the step of irradiating the radiation is gamma rays.

[0021] Effects of the Invention

[0022] According to the present invention, it is possible to provide a method for producing a glove having high tensile strength, high elongation, soft hand feel, and high stress retention rate. DETAILED DESCRIPTION

[0023] The method for producing gloves of the present invention comprises the steps of forming a dip-molded layer by dip-molding a latex composition containing a carboxyl group-containing conjugated diene rubber (A) having no monomer unit derived from isoprene and a metal compound (B) containing a divalent or higher metal, and irradiating the dip-molded layer with radiation.

[0024] Latex composition

[0025] First, the latex composition used in the production method of the present invention will be described.

[0026] The latex composition used in the present invention contains a latex of a carboxyl group-containing conjugated diene rubber (A) having no monomer unit derived from isoprene and a metal compound (B) containing a divalent or higher-valent metal.

[0027] The latex of the carboxyl-containing conjugated diene rubber (A) not having a monomer unit derived from isoprene (hereinafter, appropriately referred to as "latex of the carboxyl-containing conjugated diene rubber (A)") may be a latex of a copolymer obtained by copolymerizing a conjugated diene monomer and an ethylenically unsaturated carboxylic acid monomer and substantially containing no monomer unit derived from isoprene, and is preferably a latex of at least one rubber selected from the group consisting of a carboxyl-containing nitrile rubber (a1) not containing a monomer unit derived from isoprene, a carboxyl-containing styrene-butadiene rubber (a2) not containing a monomer unit derived from isoprene, and a carboxyl-containing butadiene rubber (a3) ​​not containing a monomer unit derived from isoprene.

[0028] The latex of the carboxyl nitrile rubber (a1) not containing monomer units derived from isoprene (hereinafter, appropriately referred to as "latex of the carboxyl nitrile rubber (a1)") is a latex of a copolymer obtained by copolymerizing an ethylenically unsaturated nitrile monomer in addition to a conjugated diene monomer and an ethylenically unsaturated carboxylic acid monomer, and substantially does not contain monomer units derived from isoprene. It may also be a latex of a copolymer obtained by copolymerizing these monomers and other ethylenically unsaturated monomers copolymerizable with them as needed.

[0029] As the conjugated diene monomer, for example, 1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene and chloroprene can be mentioned. Among these, 1,3-butadiene is preferred. These conjugated diene monomers can be used alone or in combination of two or more. The content ratio of the conjugated diene monomer unit formed by the conjugated diene monomer in the carboxyl-containing nitrile rubber (a1) is preferably 56 to 78% by weight, more preferably 56 to 73% by weight, and further preferably 56 to 70% by weight. By setting the content of the conjugated diene monomer unit to the above range, the gloves obtained by the manufacturing method of the present invention can have sufficient tensile strength, and the hand feel is more excellent and the elongation is increased. In addition, isoprene can also be considered as an example of a conjugated diene monomer, but since the monomer unit derived from isoprene will soften and deteriorate due to radiation irradiation described later, in the present invention, as the latex of the carboxyl-containing nitrile rubber (a1), a latex of a carboxyl-containing nitrile rubber that substantially does not contain a monomer unit derived from isoprene is used.

[0030] As the ethylenically unsaturated carboxylic acid monomer, there is no particular limitation as long as it is an ethylenically unsaturated monomer containing a carboxylic acid group, and examples thereof include: ethylenically unsaturated monocarboxylic acid monomers such as acrylic acid and methacrylic acid; ethylenically unsaturated polycarboxylic acid monomers such as itaconic acid, maleic acid, and fumaric acid; ethylenically unsaturated polycarboxylic acid anhydrides such as maleic anhydride and citraconic anhydride; ethylenically unsaturated polycarboxylic acid partial ester monomers such as monobutyl fumarate, monobutyl maleate, and mono-2-hydroxypropyl maleate, etc. Among these, ethylenically unsaturated monocarboxylic acids are preferred, and methacrylic acid is particularly preferred. These ethylenically unsaturated carboxylic acid monomers can also be used as alkali metal salts or ammonium salts. In addition, the ethylenically unsaturated carboxylic acid monomers can be used alone or in combination of two or more. The content ratio of the ethylenically unsaturated carboxylic acid monomer units formed by ethylenically unsaturated carboxylic acid monomers in the carboxyl-containing nitrile rubber (a1) is preferably 2 to 6.5% by weight, more preferably 2 to 6% by weight, further preferably 2 to 5% by weight, further preferably 2 to 4.5% by weight, and particularly preferably 2.5 to 4.5% by weight. By setting the content of the ethylenically unsaturated carboxylic acid monomer units in the above range, the gloves obtained by the production method of the present invention can have sufficient tensile strength, and can have a more excellent feel and a greater elongation.

[0031] The ethylenically unsaturated nitrile monomer is not particularly limited as long as it is an ethylenically unsaturated monomer containing a nitrile group, and examples thereof include acrylonitrile, methacrylonitrile, fumaronitrile, α-chloroacrylonitrile, α-cyanoethylacrylonitrile, and the like. Among them, acrylonitrile and methacrylonitrile are preferred, and acrylonitrile is more preferred. These ethylenically unsaturated nitrile monomers can be used alone or in combination of two or more. The content of the ethylenically unsaturated nitrile monomer units formed from the ethylenically unsaturated nitrile monomers in the carboxyl-containing nitrile rubber (a1) is preferably 20 to 40% by weight, more preferably 25 to 40% by weight, and further preferably 30 to 40% by weight. By setting the content of the ethylenically unsaturated nitrile monomer units to the above range, the gloves obtained by the manufacturing method of the present invention can have sufficient tensile strength, and the hand feel is more excellent and the elongation is increased.

[0032] Examples of other ethylenically unsaturated monomers copolymerizable with the conjugated diene monomer, the ethylenically unsaturated carboxylic acid monomer, and the ethylenically unsaturated nitrile monomer include: vinyl aromatic monomers such as styrene, alkyl styrene, and vinyl naphthalene; fluoroalkyl vinyl ethers such as fluoroethyl vinyl ether; ethylenically unsaturated amide monomers such as (meth)acrylamide, N-methylol (meth)acrylamide, N,N-dimethylol (meth)acrylamide, N-methoxymethyl (meth)acrylamide, and N-propoxymethyl (meth)acrylamide; methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, trifluoroethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, dibutyl maleate, dibutyl fumarate, maleate, and the like. Ethylenically unsaturated carboxylic acid ester monomers such as diethyl (meth)acrylate, methoxymethyl (meth)acrylate, ethoxyethyl (meth)acrylate, methoxyethoxyethyl (meth)acrylate, cyanomethyl (meth)acrylate, 2-cyanoethyl (meth)acrylate, 1-cyanopropyl (meth)acrylate, 2-ethyl-6-cyanohexyl (meth)acrylate, 3-cyanopropyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, glycidyl (meth)acrylate, and dimethylaminoethyl (meth)acrylate; crosslinking monomers such as divinylbenzene, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and pentaerythritol (meth)acrylate. These ethylenically unsaturated monomers can be used alone or in combination of two or more.

[0033] The content of other monomer units composed of other ethylenically unsaturated monomers in the carboxyl group-containing nitrile rubber (a1) is preferably 10% by weight or less, more preferably 5% by weight or less, and even more preferably 3% by weight or less.

[0034] The latex of the carboxyl group-containing nitrile rubber (a1) is obtained by copolymerizing a monomer mixture containing the above-mentioned monomers, preferably by emulsion polymerization. As the emulsion polymerization method, a conventionally known method can be adopted.

[0035] When the monomer mixture containing the above monomers is subjected to emulsion polymerization, commonly used polymerization auxiliary materials such as emulsifiers, polymerization initiators, molecular weight regulators, etc. can be used. The method for adding these polymerization auxiliary materials is not particularly limited, and any method such as initial one-time addition method, batch addition method, continuous addition method, etc. can be used.

[0036] There is no particular limitation on the emulsifier, and examples thereof include: nonionic emulsifiers such as polyoxyethylene alkyl ether, polyoxyethylene alkylphenol ether, polyoxyethylene alkyl ester, polyoxyethylene sorbitan alkyl ester; anionic emulsifiers such as alkylbenzene sulfonates such as potassium dodecylbenzene sulfonate and sodium dodecylbenzene sulfonate, higher alcohol sulfate ester salts, and alkyl sulfosuccinates; cationic emulsifiers such as alkyltrimethylammonium chloride, dialkylammonium chloride, and benzyl ammonium chloride; copolymeric emulsifiers such as sulfoesters of α,β-unsaturated carboxylic acids, sulfates of α,β-unsaturated carboxylic acids, and sulfoalkylaryl ethers. Among them, anionic emulsifiers are preferred, alkylbenzene sulfonates are more preferred, and potassium dodecylbenzene sulfonate and sodium dodecylbenzene sulfonate are particularly preferred. These emulsifiers can be used alone or in combination of two or more. The amount of the emulsifier used is preferably 0.1 to 10 parts by weight relative to 100 parts by weight of the monomer mixture.

[0037] There is no particular limitation on the polymerization initiator, and examples thereof include inorganic peroxides such as sodium persulfate, potassium persulfate, ammonium persulfate, potassium perphosphate, and hydrogen peroxide; organic peroxides such as diisopropylbenzene hydroperoxide, cumene hydroperoxide, tert-butyl hydroperoxide, 1,1,1,3-tetramethylbutyl hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, di-tert-butyl peroxide, di-α-cumyl peroxide, acetyl peroxide, isobutyryl peroxide, and benzoyl peroxide; and azo compounds such as azobisisobutyronitrile, azobis-2,4-dimethylvaleronitrile, and methyl azobisisobutyrate. These polymerization initiators can be used alone or in combination of two or more. The amount of the polymerization initiator used is preferably 0.01 to 10 parts by weight, and more preferably 0.01 to 2 parts by weight, relative to 100 parts by weight of the monomer mixture.

[0038] In addition, the peroxide initiator can be used in combination with a reducing agent as a redox polymerization initiator. The reducing agent is not particularly limited, and examples thereof include compounds containing metal ions in a reduced state such as ferrous sulfate and cuprous naphthenate; sulfonic acid compounds such as sodium methanesulfonate; amine compounds such as dimethylaniline, etc. These reducing agents can be used alone or in combination of two or more. The amount of the reducing agent used is preferably 3 to 1000 parts by weight relative to 100 parts by weight of the peroxide.

[0039] The amount of water used in the emulsion polymerization is preferably 80 to 600 parts by weight, particularly preferably 100 to 200 parts by weight, based on 100 parts by weight of all the monomers used.

[0040] As a method for adding monomers, for example, there can be mentioned: a method of adding the monomers to be used in a reaction vessel at once; a method of adding continuously or in batches as the polymerization proceeds; a method of adding a part of the monomers and reacting them until a specific conversion rate, and then continuously or in batches adding the remaining monomers to polymerize, etc. Any method can be adopted. In the case of adding the monomers continuously or in batches after mixing, the composition of the mixture can be fixed, or it can also be changed. In addition, each monomer can be added to the reaction vessel after premixing various monomers to be used, or it can also be added to the reaction vessel separately.

[0041] Furthermore, polymerization auxiliary materials such as a chelating agent, a dispersant, a pH adjuster, a deoxidizing agent, and a particle size adjuster may be used as necessary, and the type and amount of these materials used are not particularly limited.

[0042] The polymerization temperature during emulsion polymerization is not particularly limited, but is usually 3 to 95° C., preferably 5 to 60° C. The polymerization time is about 5 to 40 hours.

[0043] When the monomer mixture is subjected to emulsion polymerization as described above and a predetermined polymerization conversion rate is reached, the polymerization reaction is terminated by cooling the polymerization system or by adding a polymerization terminator. The polymerization conversion rate when the polymerization reaction is terminated is preferably 90% by weight or more, more preferably 93% by weight or more.

[0044] The polymerization terminator is not particularly limited, and examples thereof include hydroxylamine, hydroxylamine sulfate, diethylhydroxylamine, hydroxylamine sulfonic acid and its alkali metal salts, sodium dimethyldithiocarbamate, hydroquinone derivatives, catechol derivatives, and aromatic hydroxydithiocarboxylic acids such as hydroxydimethylphenylthiocarboxylic acid, hydroxydiethylphenyldithiocarboxylic acid, and hydroxydibutylphenyldithiocarboxylic acid, and their alkali metal salts. The amount of the polymerization terminator used is preferably 0.05 to 2 parts by weight relative to 100 parts by weight of the monomer mixture.

[0045] After the polymerization reaction is terminated, unreacted monomers may be removed as desired, and the solid content concentration and pH may be adjusted to obtain a latex of the carboxyl group-containing nitrile rubber (a1).

[0046] Furthermore, an anti-aging agent, an antiseptic, an antibacterial agent, a dispersant, etc. may be appropriately added to the latex of the carboxyl-containing nitrile rubber (a1) as required.

[0047] The number average particle size of the latex of the carboxyl group-containing nitrile rubber (a1) is preferably 60 to 300 nm, more preferably 80 to 150 nm. The particle size can be adjusted to a desired value by adjusting the amount of the emulsifier and the polymerization initiator used.

[0048] In addition, the latex of the carboxyl styrene-butadiene rubber (a2) not having a monomer unit derived from isoprene (hereinafter, appropriately referred to as "latex of the carboxyl styrene-butadiene rubber (a2)") is a latex of a copolymer obtained by copolymerizing styrene in addition to 1,3-butadiene and an ethylenically unsaturated carboxylic acid monomer as a conjugated diene monomer, and does not substantially contain a monomer unit derived from isoprene, and may also be a latex of a copolymer obtained by copolymerizing these monomers with other ethylenically unsaturated monomers copolymerizable with them as needed.

[0049] The content of butadiene units formed from 1,3-butadiene in the carboxyl group-containing styrene-butadiene rubber (a2) is preferably 56 to 78% by weight, more preferably 56 to 73% by weight, and even more preferably 56 to 68% by weight. By setting the content of butadiene units within the above range, the gloves obtained by the production method of the present invention can have sufficient tensile strength, better feel, and greater elongation.

[0050] The ethylenically unsaturated carboxylic acid monomer is not particularly limited as long as it is an ethylenically unsaturated monomer containing a carboxyl group, and for example, the same ethylenically unsaturated carboxylic acid monomer as the latex of the above-mentioned carboxyl group-containing nitrile rubber (a1) can be used. The content ratio of the ethylenically unsaturated carboxylic acid monomer unit formed from the ethylenically unsaturated carboxylic acid monomer in the carboxyl group-containing styrene-butadiene rubber (a2) is preferably 2 to 6.5% by weight, more preferably 2 to 6% by weight, further preferably 2 to 5% by weight, further preferably 2 to 4.5% by weight, and particularly preferably 2.5 to 4.5% by weight. By setting the content of the ethylenically unsaturated carboxylic acid monomer unit to the above range, the gloves obtained by the production method of the present invention can have sufficient tensile strength, and can have a more excellent feel and a greater elongation.

[0051] The content of styrene units composed of styrene in the carboxyl group-containing styrene-butadiene rubber (a2) is preferably 20 to 40% by weight, more preferably 25 to 40% by weight, and even more preferably 30 to 40% by weight. By setting the content of styrene units within the above range, the gloves obtained by the production method of the present invention can have sufficient tensile strength, better feel, and greater elongation.

[0052] As other ethylenically unsaturated monomers copolymerizable with 1,3-butadiene, ethylenically unsaturated carboxylic acid monomers and styrene as conjugated diene monomers, for example, the same ethylenically unsaturated monomers as those in the latex of the carboxyl group-containing nitrile rubber (a1) (except styrene), and other conjugated diene monomers other than 1,3-butadiene such as 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene and chloroprene, etc. The content ratio of other monomer units formed from other ethylenically unsaturated monomers in the carboxyl group-containing styrene-butadiene rubber (a2) is preferably 10% by weight or less, more preferably 5% by weight or less, and further preferably 3% by weight or less. In addition, as an example of a conjugated diene monomer other than 1,3-butadiene, isoprene can also be considered. However, since the monomer unit derived from isoprene softens and deteriorates by irradiation with radiation described later, in the present invention, as the latex of the carboxyl-containing styrene-butadiene rubber (a2), a latex of the carboxyl-containing styrene-butadiene rubber that does not substantially contain the monomer unit derived from isoprene is used.

[0053] The latex of the carboxyl-containing styrene-butadiene rubber (a2) used in the present invention is obtained by copolymerizing a monomer mixture containing the above-mentioned monomers, preferably by emulsion polymerization. As the emulsion polymerization method, the same polymerization auxiliary materials as those in the case of the carboxyl-containing nitrile rubber (a1) are used and the polymerization is carried out in the same manner.

[0054] Furthermore, to the latex of the carboxyl group-containing styrene-butadiene rubber (a2) used in the present invention, an antioxidant, an antiseptic, an antibacterial agent, a dispersant, etc. may be appropriately added as required.

[0055] The number average particle size of the latex of the carboxyl group-containing styrene-butadiene rubber (a2) used in the present invention is preferably 60 to 300 nm, more preferably 80 to 150 nm. The particle size can be adjusted to a desired value by adjusting the amount of the emulsifier and the polymerization initiator used.

[0056] In addition, the latex of the carboxyl group-containing conjugated diene rubber (a3) ​​not having a monomer unit derived from isoprene (hereinafter, appropriately referred to as "latex of the carboxyl group-containing conjugated diene rubber (a3)") is a latex of a copolymer obtained by copolymerizing a conjugated diene monomer and an ethylenically unsaturated carboxylic acid monomer and does not substantially contain a monomer unit derived from isoprene, and may also be a latex of a copolymer obtained by copolymerizing these monomers with other ethylenically unsaturated monomers copolymerizable with these monomers as needed.

[0057] The content of the conjugated diene monomer units formed from the conjugated diene monomers in the carboxyl group-containing conjugated diene rubber (a3) ​​is preferably 80 to 98% by weight, more preferably 90 to 98% by weight, and further preferably 95 to 97.5% by weight. By setting the content of the conjugated diene monomer units within the above range, the gloves obtained by the production method of the present invention can have sufficient tensile strength, better feel, and greater elongation.

[0058] The ethylenically unsaturated carboxylic acid monomer is not particularly limited as long as it is an ethylenically unsaturated monomer containing a carboxyl group, and for example, the same ethylenically unsaturated carboxylic acid monomer as the latex of the above-mentioned carboxyl group-containing nitrile rubber (a1) can be used. The content ratio of the ethylenically unsaturated carboxylic acid monomer unit formed from the ethylenically unsaturated carboxylic acid monomer in the carboxyl group-containing conjugated diene rubber (a3) ​​is preferably 2 to 10% by weight, more preferably 2 to 7.5% by weight, further preferably 2 to 6.5% by weight, further preferably 2 to 6% by weight, particularly preferably 2 to 5% by weight, and most preferably 2.5 to 5% by weight. By setting the content of the ethylenically unsaturated carboxylic acid monomer unit to the above range, the gloves obtained by the production method of the present invention can have sufficient tensile strength, and the hand feeling is more excellent and the elongation is further increased.

[0059] As the conjugated diene monomer, 1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene and chloroprene can be cited. As the conjugated diene monomer, any one of them can be used alone, or two or more can be used in combination. In addition, as an example of a conjugated diene monomer, isoprene can also be considered, but since the monomer unit derived from isoprene is softened and deteriorated by radiation irradiation described later, in the present invention, as the latex of the carboxyl-containing conjugated diene rubber (a3), a latex of a carboxyl-containing conjugated diene rubber that does not substantially contain a monomer unit derived from isoprene is used.

[0060] As other ethylenically unsaturated monomers copolymerizable with conjugated diene monomers and ethylenically unsaturated carboxylic acid monomers, for example, the same ethylenically unsaturated monomers as the latex of the above-mentioned carboxyl-containing nitrile rubber (a1) (but excluding styrene) can be cited. The content ratio of other monomer units formed by other ethylenically unsaturated monomers in the carboxyl-containing conjugated diene rubber (a3) ​​is preferably 10% by weight or less, more preferably 5% by weight or less, and further preferably 3% by weight or less.

[0061] The latex of the carboxyl-containing conjugated diene rubber (a3) ​​used in the present invention is obtained by copolymerizing a monomer mixture containing the above-mentioned monomers, preferably by emulsion polymerization. As the emulsion polymerization method, the same polymerization auxiliary materials as those in the case of the carboxyl-containing nitrile rubber (a1) are used and the polymerization is carried out in the same manner.

[0062] The latex composition of the present invention contains a metal compound (B) containing a divalent or higher-valent metal in addition to the latex of the carboxyl group-containing conjugated diene rubber (A) described above.

[0063] The metal compound (B) containing a divalent or higher-valent metal can react with the carboxyl groups contained in the carboxyl group-containing conjugated diene rubber (A) to form a crosslinked structure by metal ion bonding, thereby functioning as a crosslinking agent.

[0064] The metal compound (B) containing a divalent or higher metal is not particularly limited, and examples thereof include zinc compounds, magnesium compounds, titanium compounds, calcium compounds, lead compounds, iron compounds, tin compounds, chromium compounds, cobalt compounds, zirconium compounds, and aluminum compounds. These metal compounds (B) containing a divalent or higher metal can be used alone or in combination of two or more. Among these, metal compounds containing a trivalent or higher metal are preferred, and aluminum compounds are particularly preferred, from the viewpoint of further improving the stress retention rate of the gloves obtained by the production method of the present invention.

[0065] Examples of the aluminum compound include aluminum oxide, aluminum chloride, aluminum hydroxide, aluminum nitrate, aluminum sulfate, aluminum metal, ammonium aluminum sulfate, aluminum bromide, aluminum fluoride, aluminum sulfate potassium, aluminum isopropoxide, sodium aluminate, potassium aluminate, and sodium aluminum sulfite. Among these, sodium aluminate is preferred. These aluminum compounds can be used alone or in combination of two or more.

[0066] Furthermore, when a metal compound containing a trivalent or higher valent metal is used as the metal compound containing a divalent or higher valent metal (B), a metal compound containing a divalent metal may be used in combination. By using a metal compound containing a divalent metal in combination, the tensile strength of the gloves obtained by the production method of the present invention can be further improved. When a metal compound containing a trivalent or higher valent metal and a metal compound containing a divalent metal are used in combination, the metal compound containing a divalent metal is preferably a zinc compound, a magnesium compound, a calcium compound, or a lead compound, more preferably a zinc compound, and particularly preferably zinc oxide.

[0067] The content ratio of the metal compound (B) containing a divalent or higher metal in the latex composition used in the present invention is preferably 0.1 to 5 parts by weight, more preferably 0.5 to 2.5 parts by weight, and even more preferably 0.5 to 2.0 parts by weight relative to 100 parts by weight of the carboxyl group-containing conjugated diene rubber (A) contained in the latex. By setting the content ratio of the metal compound (B) containing a divalent or higher metal to the above range, the stability of the latex composition can be improved, and crosslinking can be sufficient when crosslinking is performed. In addition, from the viewpoint of stability and crosslinking properties of the latex composition, when a metal compound containing a trivalent or higher metal is used as the metal compound (B) containing a divalent or higher metal, the content ratio of the metal compound containing a trivalent or higher metal in the latex composition is preferably in the range of 0.1 to 1.5 parts by weight, more preferably 0.1 to 1.25 parts by weight, and even more preferably 0.1 to 1.0 parts by weight relative to 100 parts by weight of the carboxyl group-containing conjugated diene rubber (A) contained in the latex. Furthermore, from the viewpoint of stability and crosslinking properties of the latex composition, when a metal compound containing a trivalent or higher-valent metal and a metal compound containing a divalent metal are used in combination as the metal compound containing a divalent or higher-valent metal (B), the ratio of their contents, in terms of the weight ratio of "metal compound containing a trivalent or higher-valent metal:metal compound containing a divalent metal", is preferably in the range of 100:0 to 0:100, and more preferably in the range of 10:90 to 90:10.

[0068] Furthermore, the latex composition of the present invention may further contain sulfur and / or a sulfur-containing compound (C) as a crosslinking agent in addition to the metal compound (B) of a divalent or higher-valent metal.

[0069] Sulfur as a crosslinking agent is a simple sulfur substantially composed of sulfur atoms and used as a crosslinking agent for crosslinking various rubbers, and in particular, a simple sulfur that reacts with the carbon-carbon double bond portion of a conjugated diene monomer unit. Specific examples thereof include powdered sulfur, precipitated sulfur, colloidal sulfur, insoluble sulfur, and highly dispersible sulfur. In addition, sulfur-containing compounds as crosslinking agents are compounds containing sulfur atoms and used as a crosslinking agent for crosslinking various rubbers, and in particular, a compound that reacts with the carbon-carbon double bond portion of a conjugated diene monomer unit. Specific examples thereof include sulfur monochloride, sulfur dichloride, 4,4'-dithiodimorpholine, alkylphenol disulfide, 6-methylquinoxaline-2,3-dithiocarbonate, caprolactam disulfide, zinc dibutyldithiocarbamate, phosphorus-containing polysulfide, and polymer polysulfide.

[0070] The content ratio of sulfur and / or sulfur-containing compound (C) as a crosslinking agent in the latex composition of the present invention is more than 0 part by weight and less than 4 parts by weight, preferably more than 0 part by weight and less than 2.5 parts by weight, and more preferably more than 0 part by weight and less than 1.5 parts by weight, based on 100 parts by weight of the carboxyl-containing conjugated diene rubber (A) contained in the latex. According to the findings of the present inventors, by using a latex of a carboxyl-containing conjugated diene rubber substantially free of isoprene-derived monomer units as the latex of the carboxyl-containing conjugated diene rubber (A), even when sulfur and / or sulfur-containing compound (C) as a crosslinking agent is contained, the gloves obtained by the production method of the present invention can have high tensile strength, high elongation, soft feel and high stress retention, and by containing sulfur and / or sulfur-containing compound (C) as a crosslinking agent in the above content, the durability of the gloves obtained by the production method of the present invention can be further improved. On the other hand, when the content ratio of sulfur and / or the sulfur-containing compound (C) as a crosslinking agent exceeds 4 parts by weight based on the total of sulfur and the sulfur-containing compound, the tensile strength, elongation, feel and stress retention of the obtained gloves decrease.

[0071] In the latex composition used in the present invention, when a metal compound containing a trivalent or higher metal is used as the metal compound containing a divalent or higher metal (B), it is preferred to further contain at least one alcoholic hydroxy compound (D) selected from sugars (d1), sugar alcohols (d2), hydroxy acids (d3) and hydroxy acid salts (d4). By further containing such an alcoholic hydroxy compound (D), the dispersibility of the metal compound containing a trivalent or higher metal in the latex composition can be further improved, thereby making the stability of the latex composition good. As a result, the stress retention rate of the gloves obtained by the production method of the present invention can be more appropriately improved.

[0072] The alcoholic hydroxyl compound (D) used in the present invention is at least one selected from saccharides (d1), sugar alcohols (d2), hydroxy acids (d3) and hydroxy acid salts (d4). Among these, from the viewpoint of being able to further improve the effect of the present invention, it is preferred to use at least one selected from sugar alcohols (d2) and hydroxy acid salts (d4). In addition, when two or more alcoholic hydroxyl compounds (D) are used in combination, it is preferred to use at least one selected from saccharides (d1) and sugar alcohols (d2) and at least one selected from hydroxy acids (d3) and hydroxy acid salts (d4), and it is more preferred to use sugar alcohols (d2) and hydroxy acid salts (d4) in combination.

[0073] The carbohydrate (d1) is not particularly limited as long as it is a monosaccharide or a polysaccharide in which two or more monosaccharides are linked by glycosidic bonds, and examples thereof include monosaccharides such as erythrose, threose, ribose, lyxose, xylose, arabinose, allose, talose, gulose, altrose, galactose, idose, erythrulose, xylulose, ribulose, psicose, fructose, sorbose, and tagatose; monosaccharides such as trehalose, maltose, isomaltose, cellobiose, gentianose, and sucrose; Disaccharides such as maltotriose, isomaltotriose, panose, cellotriose, mannotriose, solanose, melezitose, phytose, gentioose, umbelliferyl, lactose, raffinose, etc.; homo-oligosaccharides such as maltotetraose and isomaltotetraose; tetrasaccharides such as stachyose, cellotetraose, allicinose, lycose, panose, etc.; pentasaccharides such as maltopentaose and isomaltopentaose; hexasaccharides such as maltohexaose and isomaltohexaose, etc. These may be used alone or in combination of two or more.

[0074] As sugar alcohol (d2), there is no particular limitation as long as it is a monosaccharide or a polysaccharide, and examples thereof include trisaccharide alcohols such as glycerol; tetrasaccharide alcohols such as erythritol, D-threitol, and L-threitol; pentasaccharide alcohols such as D-arabitol, L-arabitol, xylitol, ribitol, and pentaerythritol; pentaerythritol; hexasaccharide alcohols such as sorbitol, D-iditol, galactitol, D-glucitol, and mannitol; heptasaccharide alcohols such as heptol and avocado; octasaccharide alcohols such as D-erythro-D-galactose-octasaccharide alcohol, etc. These can be used alone or in combination of two or more. Among these, hexasaccharide alcohols having 6 carbon atoms are preferred, and sorbitol is more preferred.

[0075] The hydroxy acid (d3) is not particularly limited as long as it is a carboxylic acid having a hydroxyl group, and examples thereof include aliphatic hydroxy acids such as glycolic acid, lactic acid, tartronic acid, glyceric acid, 2-hydroxybutyric acid, 3-hydroxybutyric acid, γ-hydroxybutyric acid, malic acid, 3-methylmalic acid, tartaric acid, citramalic acid, citric acid, isocitric acid, leucine, mevalonate, pantoic acid, ricinoleic acid, trans-ricinoleic acid, oxalic acid, quinic acid, shikimic acid, and serine; salicylic acid, phenolic acid (homosalicylic acid, hydroxy(methyl)benzoic acid), vanillic acid, cilic acid, hydroxy Monohydroxybenzoic acid derivatives such as propionic acid, hydroxyvaleric acid, hydroxycaproic acid, hydroxyheptanoic acid, hydroxyoctanoic acid, hydroxynonanoic acid, hydroxydecanoic acid, hydroxyundecanoic acid, hydroxydodecanoic acid, hydroxytridecanoic acid, hydroxytetradecanoic acid, hydroxypentadecanoic acid, hydroxyheptadecanoic acid, hydroxyoctadecanoic acid, hydroxyeicosanoic acid, and ricinoleic acid; dihydroxybenzoic acid derivatives such as pyrocatechuic acid, dihydroxybenzoic acid, protocatechuic acid, gentisic acid, and glycosidic acid; trihydroxybenzoic acid derivatives such as gallic acid; phenylacetic acid derivatives such as mandelic acid, benzyl acid, and atrolactic acid; aromatic hydroxy acids such as cinnamic acid and hydrocinnamic acid derivatives such as myristic acid, phloric acid, coumaric acid, umbelliferous acid, caffeic acid, ferulic acid, and sinapinic acid. These may be used alone or in combination of two or more. Among these, aliphatic hydroxy acids are preferred, aliphatic α-hydroxy acids are more preferred, glycolic acid, lactic acid, tartronic acid, glyceric acid, malic acid, tartaric acid, and citric acid are further preferred, and glycolic acid is particularly preferred.

[0076] As the hydroxy acid salt (d4), there is no particular limitation as long as it is a salt of a hydroxy acid, and examples thereof include metal salts of hydroxy acids exemplified as specific examples of hydroxy acids (d3), and examples thereof include salts of alkali metals such as sodium and potassium; and salts of alkaline earth metals such as calcium and magnesium. As the hydroxy acid salt (d4), one species may be used alone, or two or more species may be used in combination. As the hydroxy acid salt (d4), an alkali metal salt of a hydroxy acid is preferred, and a sodium salt of a hydroxy acid is more preferred. In addition, as the hydroxy acid constituting the hydroxy acid salt (d4), an aliphatic hydroxy acid is preferred, an aliphatic α-hydroxy acid is more preferred, and glycolic acid, lactic acid, tartronic acid, glyceric acid, malic acid, tartaric acid, and citric acid are further preferred, and glycolic acid is particularly preferred. That is, as the hydroxy acid salt (d4), sodium glycolate is particularly preferred.

[0077] The content of the alcoholic hydroxyl compound (D) in the latex composition used in the present invention is preferably in the range of 1:0.1 to 1:50, more preferably in the range of 1:0.2 to 1:45, and even more preferably in the range of 1:0.3 to 1:30, relative to the metal compound containing a trivalent or higher metal, in terms of the weight ratio of "metal compound containing a trivalent or higher metal: alcoholic hydroxyl compound (D)". By setting the content of the alcoholic hydroxyl compound (D) in the above range, the stability of the latex composition can be further improved.

[0078] In addition, the content of the alcoholic hydroxyl compound (D) may be within the above-mentioned range relative to the content of the metal compound containing a trivalent or higher metal, but is preferably 0.03 to 15 parts by weight, more preferably 0.05 to 10 parts by weight, relative to 100 parts by weight of the carboxyl-containing conjugated diene rubber (A) contained in the latex.

[0079] The latex composition used in the present invention can be obtained by, for example, mixing a metal compound (B) containing a divalent or higher metal, and sulfur and / or a sulfur-containing compound (C) and an alcoholic hydroxyl compound (D) used as a crosslinking agent as required, in a latex of a carboxyl-containing conjugated diene rubber (A). There is no particular limitation on the method for mixing a metal compound (B) containing a divalent or higher metal, and sulfur and / or a sulfur-containing compound (C) and an alcoholic hydroxyl compound (D) used as a crosslinking agent as required, in a latex of a carboxyl-containing conjugated diene rubber (A). From the viewpoint of being able to well disperse the metal compound (B) containing a divalent or higher metal in the obtained latex composition, it is preferred that the metal compound (B) containing a divalent or higher metal and the alcoholic hydroxyl compound (D) used as required are dissolved in water or alcohol and added in the form of an aqueous solution or an alcoholic solution.

[0080] Furthermore, in the latex composition used in the present invention, in addition to the latex of the above-mentioned carboxyl-containing conjugated diene rubber (A), the metal compound (B) containing a divalent or higher metal, and sulfur and / or sulfur-containing compounds (C) and alcoholic hydroxyl compounds (D) used as crosslinking agents as needed, fillers, pH adjusters, thickeners, antioxidants, dispersants, pigments, fillers, softeners, etc. can also be formulated as desired.

[0081] The solid content concentration of the latex composition used in the present invention is preferably 10 to 40% by weight, more preferably 15 to 35% by weight. In addition, the pH of the latex composition used in the present invention is preferably 7.5 to 12.0, more preferably 7.5 to 11.0, further preferably 7.5 to 9.4, and particularly preferably 7.5 to 9.2.

[0082] Glove Manufacturing Method

[0083] The method for producing the gloves of the present invention comprises the steps of forming a dip-molded layer by dip-molding the latex composition described above, and irradiating the formed dip-molded layer with radiation.

[0084] Dip molding is a method in which a glove-shaped mold (glove mold) is dipped in a latex composition, the latex composition is deposited on the surface of the glove mold, the glove mold is pulled out from the latex composition, and then the latex composition deposited on the surface of the glove mold is dried. In addition, the glove mold may be preheated before being dipped in the latex composition. In addition, a coagulant may be used as needed before dipping the glove mold in the latex composition or after the glove mold is pulled out from the latex composition.

[0085] Specific examples of the method of using the coagulant include a method in which the glove mold before being dipped in the latex composition is dipped in a solution of the coagulant to allow the coagulant to adhere to the glove mold (anodic coagulation dipping method), a method in which the glove mold on which the latex composition is deposited is dipped in a solution of the coagulant (Teague coagulation dipping method), etc. The anodic coagulation dipping method is preferred from the viewpoint of obtaining a dip-molded layer with less uneven thickness.

[0086] Examples of the coagulant include metal halides such as barium chloride, calcium chloride, magnesium chloride, zinc chloride, and aluminum chloride; nitrates such as barium nitrate, calcium nitrate, and zinc nitrate; acetates such as barium acetate, calcium acetate, and zinc acetate; and sulfates such as calcium sulfate, magnesium sulfate, and aluminum sulfate. Among them, calcium chloride and calcium nitrate are preferred.

[0087] The coagulant is usually used in the form of a solution of water, alcohol or a mixture thereof. The concentration of the coagulant is usually 5 to 50% by weight, preferably 10 to 35% by weight.

[0088] Moreover, by subjecting the obtained dip-molded layer to heat treatment, cross-linking based on the metal compound (B) containing a divalent or higher metal is performed. At this time, the cross-linking is performed by the reaction of the metal compound (B) containing a divalent or higher metal with the carboxyl group contained in the carboxyl-containing conjugated diene rubber (A), thereby utilizing metal ion bonds. In addition, when a latex composition that also contains sulfur and / or a sulfur-containing compound (C) as a cross-linking agent is used as a latex composition, cross-linking based on sulfur and / or a sulfur-containing compound (C) is also performed simultaneously. In addition, before the heat treatment is performed, the dip-molded layer can also be immersed in water, preferably in warm water at 30 to 70°C, for about 1 to 60 minutes to remove water-soluble impurities (for example, remaining emulsifiers, coagulants, etc.). The operation of removing water-soluble impurities can be performed after the dip-molded layer is heat-treated. From the perspective of being able to more effectively remove water-soluble impurities, it is preferably performed before the heat treatment.

[0089] The crosslinking of the dip molded layer is usually carried out by heat treatment at a temperature of 80 to 150° C., preferably for 10 to 130 minutes. As the heating method, external heating using infrared rays or heated air or internal heating using high frequency can be used. Among them, external heating using heated air is preferred.

[0090] Then, the cross-linked dip-molded layer is separated from the glove mold to obtain a dip-molded body before radiation irradiation. As a separation method, it is possible to adopt a method of peeling from the glove mold by hand or using water pressure or compressed air pressure. In addition, after the separation, it can be further heated at a temperature of 60 to 120° C. for 10 to 120 minutes.

[0091] Next, the obtained dip-molded body before radiation irradiation is subjected to radiation irradiation to obtain a glove (dip-molded body after radiation irradiation). According to the manufacturing method of the present invention, by irradiating the dip-molded layer formed of the latex composition (dip-molded body before radiation irradiation), the glove obtained by the manufacturing method of the present invention can have a large elongation, a soft hand feel, and a greatly improved tensile strength, and can also have a high stress retention rate. In particular, in gloves obtained by dip molding such as surgical gloves, in addition to high tensile strength and high elongation, the feel when wearing it for operation is also particularly important. Specifically, in addition to the desired feel (stress at 500% elongation), it is also desired to effectively prevent loosening and relaxation over time after wearing (i.e., from the stress M after 6 minutes from the cessation of extension). 100 (6) The tensile stress M when the glove is stretched 100% 100 In contrast, according to the present invention, the gloves obtained by the manufacturing method of the present invention can have high tensile strength, large elongation, excellent stress (feel) at 500% elongation, and a high stress retention rate.

[0092] In addition, in the production method of the present invention, the reason why a high stress retention rate can be achieved is not very clear, but it is considered that the carbon-carbon double bonds of the conjugated diene monomer units of the carboxyl group-containing conjugated diene rubber (A) contained in the latex composition can be partially crosslinked by irradiation with radiation, and a high stress retention rate can be achieved by the formation of the crosslinks.

[0093] In addition, as the radiation to be irradiated, electromagnetic radiation such as gamma rays and X-rays, electron beams, particle radiation such as beta rays, etc. can be cited. From the viewpoint of being able to further improve the tensile strength, elongation, stress at 500% elongation, and stress retention of the gloves obtained, gamma rays or electron beams are preferred, and gamma rays are most preferred. The absorption dose of radiation such as gamma rays is preferably in the range of 1 to 500 kGy, more preferably in the range of 5 to 300 kGy, and even more preferably in the range of 10 to 100 kGy. In addition, it is desirable that the irradiation energy and time when performing gamma ray irradiation are set to appropriate conditions with reference to the target absorption dose of radiation such as gamma rays and the resistance of the irradiated object to radiation such as gamma rays. The irradiation energy of gamma rays and other radiations can be in the range of 0.1 to 10 MeV, and preferably the irradiation energy is 1.17 MeV and 1.33 MeV when cobalt 60 is used as the radiation source, and the irradiation energy is 0.66 MeV when cesium 137 is used as the radiation source. The irradiation time of the radiation such as gamma rays is not particularly limited because it is the time required for the target irradiation dose of the radiation such as gamma rays to be absorbed.

[0094] The gloves obtained by the production method of the present invention have high tensile strength, large elongation, soft hand feel and high stress retention rate, and are therefore preferably used as gloves for various purposes, and are particularly preferably used as surgical gloves.

[0095] Example

[0096] Hereinafter, the present invention will be further described based on detailed examples, but the present invention is not limited to these examples. In addition, in the following, unless otherwise stated, "parts" are weight references. In addition, the tests and evaluations are as follows.

[0097] Tensile strength, elongation at break, stress at 500% elongation

[0098] Dumbbell-shaped test pieces were prepared from the rubber gloves obtained as dip-molded products in the examples and comparative examples using a dumbbell (Die-C: manufactured by Dumbbell Co., Ltd.) according to ASTM D-412. Next, the obtained test piece was stretched at a tensile speed of 500 mm / min, and the tensile strength at break, the elongation at break, and the stress at 500% elongation were measured. The higher the tensile strength and the elongation at break, the more preferred it is. In addition, the smaller the stress at 500% elongation, the softer the hand feel, so it is preferred.

[0099] Stress retention rate

[0100] Dumbbell-shaped test pieces were prepared from the rubber gloves obtained as dip-molded products in Examples and Comparative Examples using dumbbells (Die-C: manufactured by Dumbbell Co., Ltd.) according to ASTM D-412. Tensile stress was applied to both ends of the test piece at a speed of 500 mm / min. When the test piece was stretched to 2 times (100%) in the standard section of 20 mm, the stretching was stopped and the tensile stress M was measured. 100 (0), and further, the tensile stress M after maintaining this state for 6 minutes was measured. 100 (6). Then, M 100 (6) With M 100 (0) percentage (i.e., M 100 (6) / M 100 The greater the stress retention rate, the less likely it is to cause fatigue (loosening, relaxation) associated with the use of the gloves, and therefore it is preferred.

[0101] Production Example 1 (Production of Latex of Carboxylate-Containing Nitrile Rubber (a1-1))

[0102] In a pressure-resistant polymerization reaction vessel equipped with a stirrer, 63 parts of 1,3-butadiene, 34 parts of acrylonitrile, 3 parts of methacrylic acid, 0.25 parts of tert-dodecyl mercaptan as a chain transfer agent, 132 parts of deionized water, 3 parts of sodium dodecylbenzenesulfonate, 1 part of sodium β-naphthalenesulfonic acid formalin condensate, 0.3 parts of potassium persulfate, and 0.005 parts of sodium ethylenediaminetetraacetate were added, and the polymerization temperature was maintained at 37°C to initiate polymerization. Then, when the polymerization conversion rate reached 70%, the polymerization temperature was raised to 43°C, and the reaction was continued until the polymerization conversion rate reached 95%, and then 0.1 parts of sodium dimethyldithiocarbamate was added as a polymerization terminator to terminate the polymerization reaction. Then, after unreacted monomers were distilled off under reduced pressure from the obtained copolymer latex, the solid content concentration and pH were adjusted, thereby obtaining a latex of carboxyl-containing nitrile rubber (a1-1) having a solid content concentration of 40% and a pH of 8.0. The obtained carboxyl group-containing nitrile rubber (a1-1) had a composition of 63% by weight of 1,3-butadiene units, 34% by weight of acrylonitrile units and 3% by weight of methacrylic acid units, and contained substantially no monomer units derived from isoprene.

[0103] Production Example 2 (Production of Latex of Carboxyl Group-Containing Styrene-Butadiene Rubber (a2-1))

[0104] In a pressure-resistant container equipped with a stirrer, 50 parts of deionized water, 0.3 parts of sodium dodecylbenzenesulfonate, 0.4 parts of tert-dodecyl mercaptan, 63 parts of 1,3-butadiene, 34 parts of styrene, and 3 parts of methacrylic acid were added to obtain a monomer emulsion. In another pressure-resistant polymerization reaction container equipped with a stirrer, 40 parts of deionized water, 0.2 parts of sodium dodecylbenzenesulfonate, 0.35 parts of sodium bicarbonate, and 0.05 parts of sodium ethylenediaminetetraacetate were added, and the temperature was raised to 70°C while stirring and mixing. Then, 0.5 parts of potassium persulfate was added thereto, and the monomer emulsion obtained above was immediately added, and the addition was continued for 5 hours while stirring and mixing. After the addition of the monomer emulsion is terminated, 0.2 parts of potassium persulfate are added in the form of a 3 wt % aqueous solution. When the polymerization conversion rate reaches 90%, the temperature is raised to 85°C, and the reaction is continued for 3 hours. When the polymerization conversion rate reaches 95%, 0.1 parts of sodium dimethyldithiocarbamate are added as a polymerization terminator to terminate the polymerization reaction. Then, after the unreacted monomers are distilled off from the latex of the obtained copolymer under reduced pressure, the solid content concentration and pH are adjusted to obtain a latex of carboxyl-containing styrene-butadiene rubber (a2-1) having a solid content concentration of 40 wt % and a pH of 8.0. The composition of the obtained carboxyl-containing styrene-butadiene rubber (a2-1) is: 63 wt % of 1,3-butadiene units, 34 wt % of styrene units, and 3 wt % of methacrylic acid units, and substantially no monomer units derived from isoprene are contained.

[0105] Production Example 3 (Latex containing carboxyl butadiene rubber (a3-1))

[0106] In a pressure-resistant polymerization reaction vessel equipped with a stirrer, 97 parts of 1,3-butadiene, 3 parts of methacrylic acid, 0.8 parts of tert-dodecyl mercaptan as a chain transfer agent, 132 parts of deionized water, 3 parts of sodium dodecylbenzenesulfonate, 1 part of sodium β-naphthalenesulfonic acid formalin condensate, 0.3 parts of potassium persulfate, and 0.005 parts of sodium ethylenediaminetetraacetate were added, and the polymerization temperature was maintained at 37°C to initiate polymerization. Then, when the polymerization conversion rate reached 70%, the polymerization temperature was raised to 43°C, and the reaction was continued until the polymerization conversion rate reached 95%, and then 0.1 parts of sodium dimethyldithiocarbamate was added as a polymerization terminator to terminate the polymerization reaction. Then, after unreacted monomers were distilled off under reduced pressure from the obtained copolymer latex, the solid content concentration and pH were adjusted, thereby obtaining a latex of carboxyl-containing butadiene rubber (a3-1) having a solid content concentration of 40% by weight and a pH of 8.0. The obtained carboxyl group-containing butadiene rubber (a3-1) had a composition of 97% by weight of 1,3-butadiene units and 3% by weight of methacrylic acid units, and contained substantially no monomer units derived from isoprene.

[0107] Example 1

[0108] Preparation of latex composition

[0109] A mixed aqueous solution in which 0.4 parts of sodium aluminate, 0.8 parts of sorbitol, and 0.8 parts of sodium glycolate were dissolved in water was added to 250 parts of the latex of the carboxyl-containing nitrile rubber (a1-1) obtained in Production Example 1 (based on 100 parts of the carboxyl-containing nitrile rubber (a1-1)). Then, deionized water was added thereto to adjust the solid content concentration to 30% by weight, thereby obtaining a latex composition.

[0110] Production of dip molded articles (gloves)

[0111] 30 parts of calcium nitrate, 0.05 parts of polyethylene glycol octylphenyl ether as a nonionic emulsifier and 70 parts of water were mixed to prepare a coagulant aqueous solution. Next, a ceramic glove mold preheated to 70°C was immersed in the coagulant aqueous solution for 5 seconds, pulled out, and then dried at 70°C for 10 minutes to allow the coagulant to adhere to the glove mold. Then, the glove mold with the coagulant adhered was immersed in the latex composition obtained above for 10 seconds, pulled out, and immersed in warm water at 50°C for 90 seconds to dissolve water-soluble impurities, thereby forming a dip-molded layer on the glove mold.

[0112] Next, the glove mold with the dip-molded layer formed thereon was subjected to a heat treatment at a temperature of 125°C for 25 minutes to crosslink the dip-molded layer, and the crosslinked dip-molded layer was peeled off from the glove mold to obtain a dip-molded body before γ-ray irradiation. Next, the obtained dip-molded body before γ-ray irradiation was irradiated with γ-rays using cobalt 60 as a radiation source until the absorbed radiation dose reached 30 kGy. The irradiation time was 3 hours. In this way, a dip-molded body (glove) after γ-ray irradiation was obtained. Then, the obtained dip-molded body (glove) after γ-ray irradiation was subjected to each measurement of tensile strength, elongation at break, stress at 500% elongation, and stress retention rate according to the above method. The results are shown in Table 1.

[0113] Example 2

[0114] In the preparation of the latex composition, the same procedures as in Example 1 were carried out except that 250 parts of the latex of the carboxyl-containing styrene-butadiene rubber (a2-1) obtained in Production Example 2 (calculated as 100 parts of the carboxyl-containing styrene-butadiene rubber (a2-1) was used instead of the latex of the carboxyl-containing nitrile rubber (a1-1) to obtain a latex composition having a solid content concentration of 30% by weight. Dip molding and gamma-ray irradiation were carried out in the same manner as in Example 1 to produce a gamma-ray irradiated dip-molded body (glove), which was evaluated in the same manner. The results are shown in Table 1.

[0115] Example 3

[0116] In the preparation of the latex composition, the same procedures as in Example 1 were carried out except that 250 parts of the latex of the carboxyl-containing butadiene rubber (a3-1) obtained in Production Example 3 (100 parts based on the carboxyl-containing butadiene rubber (a3-1)) were used instead of the latex of the carboxyl-containing nitrile rubber (a1-1) to obtain a latex composition having a solid content concentration of 30% by weight. Dip molding and gamma-ray irradiation were carried out in the same manner as in Example 1 to produce a gamma-ray irradiated dip-molded body (glove), which was evaluated in the same manner. The results are shown in Table 1.

[0117] Example 4

[0118] The same procedure as in Example 1 was followed except that 0.5 parts of zinc oxide was further added when preparing the latex composition to obtain a latex composition having a solid content concentration of 30% by weight. Dip molding and gamma ray irradiation were performed in the same manner as in Example 1 to produce a gamma ray irradiated dip molded article (glove), which was evaluated in the same manner. The results are shown in Table 1.

[0119] Example 5

[0120] In the preparation of the latex composition, the same procedures as in Example 1 were carried out except that 0.5 parts of zinc oxide was added instead of sodium aluminate, sorbitol and sodium glycolate to obtain a latex composition having a solid content concentration of 30% by weight. Dip molding and gamma ray irradiation were carried out in the same manner as in Example 1 to produce a gamma ray irradiated dip-molded article (glove), which was evaluated in the same manner. The results are shown in Table 1.

[0121] Example 6

[0122] A latex composition having a solid content concentration of 30% by weight was obtained in the same manner as in Example 5 except that 0.2 parts of sulfur and 0.2 parts of zinc dibutyldithiocarbamate were further added when preparing the latex composition. Dip molding and gamma ray irradiation were performed in the same manner as in Example 1 to produce a gamma ray irradiated dip-molded article (glove), which was evaluated in the same manner. The results are shown in Table 1.

[0123] Example 7

[0124] A latex composition having a solid content concentration of 30% by weight was obtained in the same manner as in Example 5 except that 2.5 parts of sulfur and 1 part of zinc dibutyldithiocarbamate were further added when preparing the latex composition. Dip molding and gamma ray irradiation were performed in the same manner as in Example 1 to produce a gamma ray irradiated dip-molded article (glove), which was evaluated in the same manner. The results are shown in Table 1.

[0125] Comparative Example 1

[0126] A dip-molded article (glove) was produced in the same manner as in Example 1, except that a latex composition having a solid content concentration of 30% by weight obtained in the same manner as in Example 1 was used and gamma-ray irradiation was not performed, and evaluation was performed in the same manner. The results are shown in Table 1.

[0127] Comparative Example 2

[0128] A dip-molded article (glove) was produced in the same manner as in Example 1 except that a latex composition having a solid content concentration of 30% by weight obtained in the same manner as in Example 2 was used and gamma-ray irradiation was not performed, and evaluation was performed in the same manner. The results are shown in Table 1.

[0129] Comparative Example 3

[0130] A dip-molded article (glove) was produced in the same manner as in Example 1 except that a latex composition having a solid content concentration of 30% by weight obtained in the same manner as in Example 3 was used and gamma-ray irradiation was not performed, and evaluation was performed in the same manner. The results are shown in Table 1.

[0131] Comparative Example 4

[0132] A dip-molded article (glove) was produced in the same manner as in Example 1 except that a latex composition having a solid content concentration of 30% by weight obtained in the same manner as in Example 4 was used and gamma-ray irradiation was not performed, and evaluation was performed in the same manner. The results are shown in Table 1.

[0133] Comparative Example 5

[0134] A dip-molded article (glove) was produced in the same manner as in Example 1 except that a latex composition having a solid content concentration of 30% by weight obtained in the same manner as in Example 5 was used and gamma-ray irradiation was not performed, and evaluation was performed in the same manner. The results are shown in Table 1.

[0135] Comparative Example 6

[0136] A dip-molded article (glove) was produced in the same manner as in Example 1 except that a latex composition having a solid content concentration of 30% by weight obtained in the same manner as in Example 7 was used and gamma-ray irradiation was not performed, and evaluation was performed in the same manner. The results are shown in Table 1.

[0137] Reference Example 1

[0138] In the preparation of the latex composition, 250 parts of natural rubber latex (100 parts in terms of natural rubber) was used instead of the latex of the carboxyl nitrile rubber (a1-1), and 0.5 parts of zinc oxide, 1 part of sulfur and 1 part of zinc dibutyl dithiocarbamate were added instead of sodium aluminate, sorbitol and sodium glycolate. A latex composition having a solid content concentration of 30% by weight was obtained in the same manner as in Example 1. Dip molding and gamma ray irradiation were performed in the same manner as in Example 1 to produce a dip-molded body (glove) after gamma ray irradiation, and evaluation was performed in the same manner. The results are shown in Table 2.

[0139] Reference Example 2

[0140] A dip-molded article (glove) was produced in the same manner as in Example 1, except that a latex composition having a solid content concentration of 30% by weight obtained in the same manner as in Reference Example 1 was used and gamma-ray irradiation was not performed, and evaluation was performed in the same manner. The results are shown in Table 2.

[0141] [Table 1]

[0142]

[0143] [Table 2]

[0144] Table 2

[0145] Reference Example 1 Reference Example 2 Preparation of latex composition Natural rubber (unit) 100 100 Sodium aluminate (part) - - Zinc oxide (parts) 0.5 0.5 Sulfur (parts) 1 1 Zinc dibutyl dithiocarbamate (part) 1 1 Sorbitol (part) - - Sodium glycolate (part) - - Whether there is γ-ray irradiation have none Evaluation of dip molded products (gloves) Tensile strength(MPa) 23.1 20.5 Elongation at break (%) 980 1020 Stress at 500% elongation (MPa) 1.4 1.2 Stress retention rate (%) 79 85

[0146] From Table 1, the following can be confirmed.

[0147] That is, by comparing Examples 1 to 7 with Comparative Examples 1 to 6, it was confirmed that by irradiating a dip-molded article obtained by using a latex containing a carboxyl group-containing conjugated diene rubber (A) not having a monomer unit derived from isoprene and a metal compound (B) containing a divalent or higher metal with gamma rays, the elongation at break was large, the soft hand feeling (stress at 500% elongation was small) could be well maintained, and the tensile strength and stress retention rate could be greatly improved. That is, according to the present invention, the strength required for gloves can be improved, and it was confirmed that the occurrence of fatigue (loosening, relaxation) accompanying the use of gloves can be appropriately prevented.

[0148] From Table 2, the following can be confirmed.

[0149] That is, by comparing Reference Example 1 and Reference Example 2, it was confirmed that the stress retention rate decreased when the dip-molded body obtained using the latex composition containing the natural rubber latex containing polyisoprene as the main component was irradiated with gamma rays.

[0150] Therefore, it was confirmed that by using a carboxyl group-containing conjugated diene rubber having no monomer unit derived from isoprene as the carboxyl group-containing conjugated diene rubber in the production method of the present invention, a glove having high tensile strength and elongation, soft hand feel and high stress retention can be obtained.

[0151] In addition, the dip-molded articles obtained in Reference Examples 1 and 2 contain proteins that cause allergic symptoms in humans because they use natural rubber latex. Therefore, their use is restricted when used as dip-molded articles that come into direct contact with the mucous membranes or organs of living organisms, especially for gloves.

Claims

1. A method for manufacturing gloves, comprising the following steps: A step of forming a dip-molded layer by dip-molding a latex composition containing a carboxyl group-containing conjugated diene rubber A and a metal compound B containing a divalent or higher metal, wherein the carboxyl group-containing conjugated diene rubber A does not have a monomer unit derived from isoprene, and a step of irradiating the dip molded layer with radiation, The radiation in the step of irradiating radiation is gamma rays, and the radiation is irradiated in such a way that the absorbed radiation dose is 1 to 100 kGy. By the step of irradiating the radiation, the carbon-carbon double bonds of the conjugated diene monomer units of the carboxyl group-containing conjugated diene rubber A are partially crosslinked. The content ratio of the metal compound B containing a divalent or higher-valent metal in the latex composition is 0.1 to 2.0 parts by weight based on 100 parts by weight of the carboxyl group-containing conjugated diene rubber A contained in the latex.

2. The method for manufacturing gloves according to claim 1, wherein: The carboxyl group-containing conjugated diene rubber A is at least one selected from the group consisting of a carboxyl group-containing nitrile rubber a1, a carboxyl group-containing styrene-butadiene rubber a2, and a carboxyl group-containing butadiene rubber a3.

3. The method for producing gloves according to claim 1 or 2, wherein: The metal compound B containing a divalent or higher-valent metal contains a metal compound containing a trivalent or higher-valent metal.

4. The method for producing gloves according to claim 1 or 2, wherein: As the metal compound B containing a metal having a valency of three or more, a metal compound containing a metal having a valency of two or more and a metal compound containing a metal having a valency of two or more are used together.

5. The method for manufacturing gloves according to claim 3, wherein: The metal compound containing a metal having a valence of three or more is an aluminum compound.

6. The method for manufacturing gloves according to claim 3, wherein: The latex composition further contains at least one alcoholic hydroxyl compound D selected from the group consisting of sugars d1, sugar alcohols d2, hydroxy acids d3, and hydroxy acid salts d4.

7. The method for producing gloves according to claim 1 or 2, wherein: The latex composition contains sulfur and / or a sulfur-containing compound C as a crosslinking agent, wherein the ratio of the sulfur and / or the sulfur-containing compound C as a crosslinking agent is more than 0 parts by weight and less than 4 parts by weight in terms of the total amount of sulfur and the sulfur-containing compound relative to 100 parts by weight of the carboxyl group-containing conjugated diene rubber A contained in the latex.

Citation Information

Patent Citations

  • Dip molding latex, method for producing the latex, dip molding composition, and dip molded product

    JP2003165814A